A prospect-theory model of voter turnout - Oliver Herrmann; Richard Jong-A-Pin; Lambert Schoonbeek (Center for Economic Studies and ifo Institute (CESifo), 2019)
We incorporate prospect-theory preferences in a game-theoretic model to study voter turnout. We show that voter turnout is heavily affected by agents having subjective reference points with respect to the vote or abstain decision and their subjective probability weighting in the decision-making process. Using empirically based parameter values, we show that our model has lower prediction error than other game-theoretic models with standard expected-utility preferences. We also find that our model maintains desirable comparative statics effects and leads to higher turnout predictions in larger electorates.
Keywords: D72; 330; voting behavior; Downsian paradox; prospect-theory preferences